The conversion of ether bonds to hydroxyl via a base-promoted rearrangement of cyclic phosphine oxides. Issue 20 (17th August 2021) - Li, Zhan-Cai; Zhang, Yu; Yan, Bing-Xia; Wang, Xiao-Ning; Zhai, De-Hua; Li, Qiang; Zheng, Hong-Xing; Zhao, Chang-Qiu
Abstract : Biphenyl derived secondary phosphine oxides having 2′-hydroxyl were prepared. Abstract : Biphenyl derived secondary phosphine oxides having 2′-hydroxyl were prepared. The compounds were converted to hydroxymethyl phosphine oxides when reacted with formaldehyde. After chlorination and cyclization, a series of P, O-heterocycles were obtained. When treated with LDA, a rearrangement occurred to stereoselectively afford hydroxyl substituted cyclic phosphines. The rearrangement was proposed to occur via intra-molecular aromatic substitution (SN Ar) reactions, with an attack of a carbon anion on alkoxyl on an adjacent benzene cycle. P -Stereogenic secondary phosphine oxide was stereospecifically converted to a P, C, axial -stereogenic P-cycle.